A New Approach Using Aromatic-Solvent-Induced Shifts in NMR Spectroscopy to Analyze β-Lactams with Various Substitution Patterns - Chavelas-Hernández, Leticia; Valdéz-Camacho, Jonathan R.; Hernández-Vázquez, Luis G.; Dominguez-Mendoza, Blanca E.; Vasquez-Ríos, María G.; Escalante, Jaime (Synlett, 2020)
The chemical shifts of protons depend not only on the properties of the solute molecule but also on the medium in which the solute resides. A series of β-lactams with various substitution patterns were synthesized to study aromatic-solvent-induced shifts (ASISs) in chloroform and benzene by using 1H NMR spectroscopy. The results agreed with those obtained by theoretical density functional theory calculations. The protons of the β-lactam ring are the most affected by the ASIS effect, and they tend to overlap due to the anisotropic effect of benzene.
Keywords: lactams; NMR spectroscopy; solvent effect